Esophageal variceal ligation plus sclerotherapy vs. ligation alone for the treatment of esophageal varices - Yue, Xiaofen; Wang, Zeyu; Li, Jianbiao; Guo, Xiaoling; Zhang, Xiehua; Li, Shengnan; Lv, Hongcheng; Hu, Dongsheng; Ji, Xiangjun; Li, Shuang; Lu, Wei (Frontiers in Surgery, 2022)
Background This study aimed to evaluate the efficacy and adverse events of esophageal variceal ligation (EVL) vs. EVL combined with endoscopic injection sclerosis (EIS) in the therapy of esophageal varices. Methods Patients from January 2017 to August 2021 who received EVL alone (control group) or EVL plus EIS (intervention group) were enrolled in this retrospective study. Efficacy, including rebleeding (clinically hematemesis or melena, confirmed by endoscopy as esophagogastric varices bleeding), variceal recurrence rate (the presence of esophagogastric varices which is needed to be treated again) the number of sessions performed to complete eradication of varices, and safety (adverse events) were compared. The variceal recurrence-associated factors were derived by univariate and multivariate logistic regression analyses. Results The variceal recurrence and rebleeding rate in the intervention group showed significantly lower than the control group (2.6% vs 10.3%, P = 0.006 and 20.7% vs 37.5%, P = 0.029, P = 0.006, respectively, in the 12-month follow-up). The adverse events (fever, chest pain, swallowing, and esophageal stricture) showed no significant difference between the two groups (P > 0.05). Further research showed that the efficacy of the intervention group was better than the control group only achieved in prophylactically endoscopic treatment patients. The diameter of esophageal varices and gastric varices co-exist showed significant effects on variceal recurrence in intervention group [odds ratio (OR) = 15.856; 95% confidence interval (CI), 1.709–160.143; P = 0.016 and OR = 4.5; 95% CI, 1.42–20.028; P = 0.021; respectively]. Conclusions The intervention group may obtain lower recurrence, rebleeding rate, and fewer sessions performed to complete eradication of varices (number of sessions) and similar incidence of adverse events, especially for prophylactically treatment. Among the intervention group, the diameter of esophageal varices and gastric varices were closely associated with variceal recurrence.